Comparative analysis of the impact of selected anesthesia methods on the cognitive function of patients undergoing ophthalmic surgery - V.M. Sakovych; G.S. Dorofeeva; V.P. Aleksieiev; O.V. Aleksieieva; I.A. Drapak (Journal of Ophthalmology, 2023)
Background: Anesthesiologists should not only save patient’s life as a process, but also enable the patient to recover his/her social life after surgery, given increased longevity, high social activity throughout life, and increased use of technical equipment in everyday life.